Functionalization of smart recycled asphalt mixtures: a sustainability scientific and pedagogical approach - Rocha Segundo, Iran (2022)
The sustainable development of our societies demands strong efforts on scientific and technological research while informing and educating students and the general population. Air pollution and road safety hazards constitute two main public health problems that are insufficiently addressed pedagogically. With this work, we aim to contribute to tackeling the problem by presenting the results of scientific research on the development of photocatalytic, superhydrophobic, and self-cleaning recycled asphalt mixtures to achieve an eco-social friendly and smart material able to mitigate socioenvironmental impacts. The functionalization of asphalt is implemented by spraying particles’ solutions over a conventional AC 10, then evaluated by dye degradation and wettability. Firstly, different particles’ solutions (with nano-TiO2 and/or micro-PTFE under water, ethyl alcohol, and dimethyl ketone) were sprayed to select the best solution (BS), which was composed of TiO2-PTFE (4 g/L each) in ethyl alcohol. Two successive spraying coatings (diluted epoxy resin and BS) were performed over conventional and recycled AC 10 (with reclaimed asphalt pavement and steel slags). Their efficiency decreases with the highest resin amounts. The best results were obtained with 0.25 g resin and BS. For the lowest resin amount, all mixtures achieved superhydrophobicity and performed similarly regarding wettability.